Advances in the design of a methodology for the identification, characterization, and assessment of and intervention in the industrial landscape - Alba Dorado, María Isabel; Romero de Oliveira, Eduardo [UNESP] (Springer Nature, 2022)
The process of degradation and abandonment to which many landscapes generated by industrial decay are currently exposed, together with the lack of conceptual and methodological means required for the study of and intervention in these landscapes, would suggest that the existing approach requires revision. In this context, the aim of this article is to detail the progress being made by a research project, the objective of which is to design a methodology for the analysis and enhancement of and intervention in these industrial heritage landscapes. The project proposes a series of methodological improvements and innovations that take into account, among other issues, the specificity and identity of these landscapes, their dynamic, highly anthropized nature, the diversity of scales involved, and so forth, using a method that integrates an interdisciplinary approach, emphasizes citizen participation and incorporates the use of digital tools.
Keywords: Cultural landscape; Industrial heritage; Post-industrial sites; Social participation; Sustainable development; Urban renewal